Infection surveillance analysis of catheter associated urinary tract infections in obstetrics and gynecology department of a tertiary care hospital of Central India - Jain, Mudita; Kaushal, Rituja; Bharadwaj, Malini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The prevalence of catheter associated urinary tract infections (CAUTIs) in the catheterized patients in acute care settings (catheter used for <7 days) is 3%-7%, in patients who require a urinary catheter for >7 days, it is up to 25% and it approaches 100% after 30 days. As device related hospital acquired infections are imposing major threats in surgical realm of medical sciences, this study was undertaken with the objective to asses catheter related urinary tract infections magnitude. Methods: This study was undertaken in a tertiary care setting of Obstetrics and Gynecology Department of a Central Indian city. It is a prospective study conducted over a full year span from April 2016 to March 2017. Results: CAUTI was calculated as 8.95 per thousand catheter days for the whole study period. Out of the total number of 18 urinary isolates, E. Coli and Enterococcus species were more commonly implicated. Conclusions: In order to restraint the enigma, a multidisciplinary integrated approach including periodic training sessions for all health care workers based on bundled care interventions supervisory checklists etc. is needed. Aseptic techniques along with IDSA (Infectious disease society of America) guidelines/other similar protocols are recommended to bring down overall prevalence. Prudent use of antibiotics is to be accorded as per antibiotic stewardship program to combat drug resistance.